Zum Stellenwert von Theorie und quantizifierenden Techniken im Forschungsprozeß der Geographie - Hantschel, Roswitha; Tharun, Elke (ERDKUNDE, 1977)
The statements under consideration are the result of the attempt to find a concept for the author’s own scientific work by critical reading and discussion of general literature in epistemology and the philosophy of science. An attempt was made at the same time to set the positions taken up by the two most important contemporary movements against one another: that of the analytical philosophy of science, which legitimizes formalization, against that of the critical theory, which places a renewed emphasis on the link with action. An attempt has been made to allow what is held in common by the seemingly contradictory positions to emerge, and to adopt those theses which appeared - subjectively - to be acceptable